Independent Candidacy and Electoral Reform: New Nation Movement NPC v President of the Republic of South Africa - Pretorius, Loot (Potchefstroom Electronic Law Journal, 2022)
In the New Nation case, the Constitutional Court declared the provisions of the Electoral Act that prevent independent candidates from competing in provincial and national elections unconstitutional. It ruled that the impugned provisions violated independent candidates’ constitutional rights to stand for public office, to freedom of association and to dignity. In a minority judgment, Froneman J disagreed and held that the Constitution contemplates a right to contest elections as a party-nominee only. The differences between the majority and minority judgments are largely the result of distinct interpretive approaches. The majority conducted an analysis of the right to stand for public office within a restricted textual framework that has the potential to disturb the harmonious inter-relationship between the right and the electoral and parliamentary framework for its realisation. This result flows from the fact that the Constitution still reflects the exclusively party-based electoral and parliamentary systems of its predecessor in several important respects. At best, this situation may result in independents being largely at the mercy of political parties for meaningful execution of their legislative and oversight obligations. At worst, they may be excluded from exercising core parliamentary functions altogether. Therefore, to avoid disturbing the normative coherence between the right to stand for public office, the foundational democratic values, and the electoral and parliamentary arrangements, constitutional amendments appear to be necessary for the implementation of the court’s order. In any event, expectations about the contribution to electoral reform of allowing independents to contest elections must be tempered by the low political impact of independent representatives on governance, as well as the ambivalence surrounding the democratic functionality of independent candidacy, when measured against the values of transparency and accountability.